The first example of a one-step synthesis of 2'-O-acetyl aryl-d-glucopyranosides - Stepanova E. V. Elena Vladimirovna; Belyanin M. L. Maksim L'vovich; Filimonov V. D. Viktor Dmitrievich; Valiev R. R. Rashid Rinatovich; Margit G. Gruner; Rogachev V. O. Victor Olegovich (2015, 2015)
Title screen